Efeito Do Tratamento De Sementes De Cardeiro (Scleronema Micranthum Ducke) Com Fungicida E Inseticida Na Germinação - Nunes, Mario Ney; Varela, Vania Palmeira (Acta Amazonica, 1992)
An experiment was conducted in order to test the effects Aldrin (0,3% e 0,6%) and freniate (0,2% and 0,4%) afone and in various combination on the germination of Cardeiro (Scleronema micranthum Ducke) seeds. Different treatments of the seeds allowed the following conclusions: a) light doses of Aldrin have a stimulant effect on seed germination; b) the percentage of the germinating seeds was reduced with beniate applied in doses exceding 0,2%; c) the germination percentage was increased when seeds were treated with 0,4% Benlate in combination with Aldrin, except when Aldrin was applied in doses greater than 0,3%; d) increasing the dose of freniate in combination with 0,3% Aldrin resulted in a higher percentage of germinating seeds; e) prejudicial effects on seed germination were provoked by increasing the dose of freniate in combination with 0,6% Aldrin.